Synthesis and antibacterial activity of ionic liquids and organic salts based on penicillin g and amoxicillin hydrolysate derivatives against resistant bacteria - Ferraz, Ricardo (2020)
Fundacao para a Ciencia e Tecnologia through projects (PTDC/QUI-QOR/32406/2017, PEst-C/LA0006/2013) and PTDC/BTM-SAL/29786/2017, and one contract under Investigador FCT (L.C.B.). ZP thanks to Fundacao para a Ciencia e a Tecnologia, MCTES, for the Norma transitoria DL 57/2016 Program Contract. This work was also supported by the Associate Laboratory for Green Chemistry, which is financed by national funds from FCT/MEC, UIDB/50006/2020 and co‐financed by the ERDF under the PT2020 Partnership Agreement (POCI‐01‐ 0145‐FEDER‐007265). The authors also thank Solchemar company for support.